2017
DOI: 10.1007/s10533-017-0340-y
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of macronutrients to the concurrent effects of enhanced temperature and atmospheric pCO2 in representative shelf sea sediment habitats

Abstract: Fundamental changes in seawater carbonate chemistry and sea surface temperatures associated with the ocean uptake of anthropogenic CO 2 are accelerating, but investigations of the susceptibility of biogeochemical processes to the simultaneous occurrence of multiple components of climate change are uncommon. Here, we quantify how concurrent changes in enhanced temperature and atmospheric pCO 2 , coupled with an associated shift in macrofaunal community structure and behavior (sediment particle reworking and bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 85 publications
(113 reference statements)
0
13
0
Order By: Relevance
“…Regarding nitrates, results suggest a delay in response to the warming, with an increasing nitrate release 1-week after the heatwave occurrence. However, we could not relate it with the bioturbation, nor with the specific functional behaviour of the species that compose the benthic community, as in 35 . We would need to extend the experiment to conclude some warming effect, as the impact of warming in species' bioturbation and nutrient generation may only manifest for prolonged periods 34 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Regarding nitrates, results suggest a delay in response to the warming, with an increasing nitrate release 1-week after the heatwave occurrence. However, we could not relate it with the bioturbation, nor with the specific functional behaviour of the species that compose the benthic community, as in 35 . We would need to extend the experiment to conclude some warming effect, as the impact of warming in species' bioturbation and nutrient generation may only manifest for prolonged periods 34 .…”
Section: Discussionmentioning
confidence: 96%
“…Bioturbation mediated by macrofauna generally increases sediments' oxygenation and may be an essential trigger for nutrient release 35 , 39 , 48 , 49 . However, the variation trends in the nutrient release data in this study were not directly correlated with macrofauna's bioturbation, as also concluded by 33 , 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, evidence suggests that variation in the functional attributes of communities [37][38][39] can affect carbon-and nutrient-cycling processes more than species diversity can [40]. Anticipated changes in the abundance, distribution, and behavior of functionally important species in response to global environmental change [2,41,42] raise concerns about significant alteration of ecosystem function and services, given the strong interlinkages among seabed functioning [43] and ocean productivity. Local-regional-level studies that consider faunal mediation of carbon cycling from shallow to deep seafloor ecosystems highlight the potential importance of including organisms in global carbon models and considering the contributions of different seabed environments [44].…”
Section: The Role Of Seafloor Biotamentioning
confidence: 99%
“…It is important to account for differences in sediment habitat when assessing biogeographic patterns, as for example much of the functioning is undertaken by physical processes rather than biological processes in sand habitats, whilst the reverse is true in muddy sediments (Sciberras et al 2017;Hale et al 2017;Godbold et al 2017). Accounting for spatial differences even at smaller scale of distinct seafloor morphologies was found crucial for improving management of goods and services delivered by marine ecosystems (Zeppilli et al, 2016).…”
Section: Potential Environmental Drivers Of Biogeographic Patterns Ofmentioning
confidence: 99%